Chemical constituents of Kopsia singapurensis Ridl. and their antiplasmodial activity / Noor Aimi bt Othman @ Ghazali - Othman, Noor Aimi (2012)
The chemical constituents of the Malaysian Apocynaceae Kopsia singapurensis Ridl. (KL5334) has been carried out in this study. Seven substances ; methyl sinapate (IUPAC name : (E)-methyl-3-(4-hydroxy-3,5-dimethoxyphenyl) acrylate 82, leuconolam 83, trans-2,2`-dicarboxyazobenzene dioxide 84, lonicerine 85, 15-hydroxykopsinine 86, singapurine 87 and N4-hydroxymethyl kopsinic acid 88, have been isolated using several chromatography techniques such as column chromatography and thin layer chromatography from the bark of Kopsia singapurensis Ridl.. Methyl sinapate 82 and trans-2,2`-dicarboxyazobenzene dioxide 84 are new natural compounds while singapurine 87 and N4-hydroxymethyl kopsinic acid 88 are two new indole alkaloids. The structures of the isolated compounds were elucidated by using spectroscopic techniques namely NMR (1H, 13C and 2D), UV, IR and mass spectrometry.